ANALISIS PENDAPATAN USAHATANI MONOKULTUR KENTANG DAN TUMPANGSARI KENTANG-CARICA DESA SEMBUNGAN KECAMATAN KEJAJAR KABUPATEN WONOSOBO - Diar Rizkiqa Herliani; Djoko Sumarjono; Bambang Mulyatno Setiawan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2019)
Cropping petterns of farmers in Sembungan Village are monoculture and intercropping. This study examines more profitable and can evaluate cropping patterns using intercropping and monoculture. Farmers in Sembungan Village have not paid attention to operational costs, net income and sustainability feasibility as measured by the R/C ratio. This reasearch aims to analyze net income, profitability and R/C ratio of the planting system potato monoculture and the planting system potato-carica intercropping. The reasearch method used survey method location was decided by purposive method. The number of respondents decided by nonprobability sampling that is sampling quota. The samples determined by 30 potato farmers and 30 potato-carica farmers. Respondent decided by snowball sampling. The analyze used two-sample assuming equal variences used microsoft excel. The results of reasearch that the net income of potato-carica intercropping significantly higher than the net income of potato monoculture. Net income of potato-carica intercropping is Rp 17,386,588.2 and Net income of potato monoculture is Rp 7,537,404.3. Profitability of potato-carica intercropping significantly higher than the profitability of potato monoculture. Profitability of potato-carica intercropping is 60.39% and profitability of potato monoculture is 44.07%. R/C ratio of potato-carica intercropping higher than R/C ratio of potato monoculture. R/C ratio of potato-carica intercropping is 1.60 and R/C ratio of potato monoculture is 1.44.